2016
DOI: 10.17015/ejbe.2016.017.07
|View full text |Cite
|
Sign up to set email alerts
|

Banking Regulation and Determinants of Banks’ Profits: Empirical Evidence from Turkey

Abstract: The crises that are frequently observed in the banking industries of emerging markets which affect banks' profits necessitate regulations and supervision of these markets. This paper investigates the determinants of Turkish banks' profits and the effects of the regulations implemented in this industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Furthermore, according to (El-Kassem, 2017) found that non-performing loan has a significantly and negatively affect the ROAA of banks in Qatar; Likewise according to (Sinha & Sharma, 2016) states that credit risk has a negatively impacts the bank profitability in Commercial Bank in India; And according to (Petria et al, 2015), found that credit risk has influence on bank profitability both on ROAA and ROAE in EU 27 banking systems; Likewise according to (Eduardus, Husnan, & Hanafi, 2012) states that credit risk has insignificant impact on bank profit efficiency. (Erdogan & Aksoy, 2016) found that the increase in non-performing loans among total loans, it was observed that profitability is inclined to decrease commercial banks' profits in Turkey. Although it is not in line with (Buchory, 2016) which state that NPL has a positive effect on profitability, the effect is not significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, according to (El-Kassem, 2017) found that non-performing loan has a significantly and negatively affect the ROAA of banks in Qatar; Likewise according to (Sinha & Sharma, 2016) states that credit risk has a negatively impacts the bank profitability in Commercial Bank in India; And according to (Petria et al, 2015), found that credit risk has influence on bank profitability both on ROAA and ROAE in EU 27 banking systems; Likewise according to (Eduardus, Husnan, & Hanafi, 2012) states that credit risk has insignificant impact on bank profit efficiency. (Erdogan & Aksoy, 2016) found that the increase in non-performing loans among total loans, it was observed that profitability is inclined to decrease commercial banks' profits in Turkey. Although it is not in line with (Buchory, 2016) which state that NPL has a positive effect on profitability, the effect is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study support previous research by (Islam & Rana, 2017); (Menicucci & Paolucci, 2016); (Samad, 2015); (Buchory, 2016); (Egbe & Collins, 2014); (Yigermal, 2017) which states that the LDR has an effect on profit. Then according to (Islam & Rana, 2017); (El-Kassem, 2017); (Sinha & Sharma, 2016); (Petria et al, 2015); (Eduardus et al, 2012), (Erdogan & Aksoy, 2016); and (Buchory, 2016) which states that NPLs have an effect on profit. And according to (Ramadan et al, 2011); (Le Thanh et al, 2017); (Islam & Rana, 2017); (El-Kassem, 2017); (Sinha & Sharma, 2016); and (Buchory, 2016) found that that operating efficiency as measured by operating expense to operating income had a negative effect on profitability significantly has an effect on profit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies on bank capital were conducted by Kosmidou et al (2005), Davydenco (2011), Rahman et al (2015), Erdogan and Aksoy (2016), Anarfi (2016), Merin (2016), Kadioglu et al (2017), Anggraini and Prastiwi (2019), Harbi (2019), Golubeva et al (2019), andSunaryo (2020), who found that capital has a positive effect on bank performance. However, Supriyono andHerdhayinta (2019), andHasan et al (2020), found a negative effect, while Heffernan and Fu (2010) and Silaban (2017, found no effect of capital on bank performance.…”
Section: Capitalmentioning
confidence: 99%
“…Research on loan to deposit ratio was conducted by Kosmidou et al (2005), Samad (2015), Rahman et al (2015), Erdogan and Aksoy (2016), Anarfi (2016), Anggraini and Prastiwi (2019), and Supriyono and Herdhayinta (2019), found that the loan to deposit ratio has a positive effect on bank performance. However, the result of research from Davydenco (2011), andHarbi (2019), found that the loan to deposit ratio has a negative effect on the bank performance.…”
Section: Liquiditymentioning
confidence: 99%